Yuk-Gunja-Tang attenuates neuronal death and memory impairment via ERK/CREB/BDNF signaling in the hippocampi of experimental Alzheimer’s disease model - Pak, Malk Eun; Yang, Hye Jin; Li, Wei; Kim, Jae Kwang; Go, Younghoon (Frontiers in Pharmacology, 2022)
Yuk-Gunja-Tang (YG) is the Korean traditional medicine in East Asia for gastrointestinal disorders. In the present study, we determined the protective effects of YG on glutamate-induced cytotoxicity in HT22 hippocampal neuronal cells and mice with scopolamine-induced memory impairment. In vitro assessments were performed using a cell viability assay, flow cytometry, and Western blotting, while in vivo assessments were performed in C57BL/6 mice administered with YG for 7 days and injected with scopolamine (1 mg/kg) for 7 days. We assessed the memory function using the Y-maze, novel object recognition, and passive avoidance tests. Protein expression analyses and histological analyses were performed using hippocampal tissues. YG treatment significantly restored cell viability against glutamate-induced apoptosis. It significantly suppressed glutamate-induced reactive oxygen species accumulation and mitochondrial dysfunction. It also increased Bcl-2 protein expression and decreased HO-1 protein expression. It activated the extracellular signal-regulated kinase/cAMP response element binding protein (ERK/CREB) signaling pathway and increased the expression of brain-derived neurotrophic factor (BDNF) under excitotoxic conditions. In the scopolamine-injected mice, YG ameliorated memory impairment in the Y-maze, novel object recognition, and passive avoidance tests; restored dysfunction in the acetylcholine, acetylcholinesterase expression levels; reduced neuronal damage in Nissl staining; and increased BDNF and phosphorylated ERK and CREB levels in Western blotting and immunofluorescence staining. Thus, YG exerted neuroprotective effects by activating ERK/CREB/BDNF signaling in the hippocampus, indicating its potential cognition-enhancing effects, especially in Alzheimer’s disease.